Curcumin-loaded graphene oxide quantum dots enhance otoprotective effects via blocking cuproptosis - Hu, An; Zhang, Jian-Wei; Yang, Li-Yun; Qiao, Pei-Pei; Lu, Dan; Yu, Ya-Feng (Frontiers in Bioengineering and Biotechnology, 2023)
Abstract Background: Cisplatin (CIS) is widely used to treat various cancers but can cause ototoxicity and sensory hair cell loss in the inner ear. Copper induces an excessive production of reactive oxygen species (ROS) in hair cells, leading to the development of various antioxidants. Methods and Results: This study aimed to evaluate the potential antioxidant properties of curcumin (CUR) in the inner ear organ of corti-1 cells (OC1) and animal models (zebrafish and guinea pigs). Graphene oxide quantum dots (GOQDs) enabled CUR to penetrate the round window membrane (RWM) and maintain the concentration in the perilymph after inner ear administration. The results showed that CUR/GOQDs had favorable biocompatibility and strongly affected ROS generation induced by CIS in OC1 cells. DCFHDA Green staining demonstrated that CUR/GOQDs successfully reversed the decrease in mitochondrial membrane potential induced by CIS in vitro and rescued cells from early cuproptosis, which was confirmed by FDX1 staining. Additionally, the experiment found that CUR decreased the expression of cuproptosis proteins (FDX1, LIAS, and LIPT1) and increased the expression of the Bcl-2 protein. Conclusions: The results demonstrate that CUR/GOQDs is a promising therapeutic agent that can prevent CIS-induced ototoxicity by blocking the cuproptosis signal pathway.